The future of commercial law : ways forward for change and reform - Future of commercial law (Conference) (2017 : University of Durham); Akseli, N. Orkun (Nazim Orkun); Linarelli, John; Society of Legal Scholars; Durham Law School (Oxford ; Hart, 2020)
"The reform of commercial law through harmonisation, unification, codification and other means remains one of the most important projects in developing the institutional architecture for the global economy. This edited collection engages with the challenges and contributes to a greater understanding of the problems faced by states, international organisations, and private sector actors in this ongoing reform project for commercial law. The volume takes stock of the project to-date and looks towards restructuring of the agenda to deal with new challenges. The primary aim of the collection is to understand the future of commercial law reform in a way that offers ideas and strategies for innovation in commercial law reform in substance as well as in methodologies for project selection and evaluation. In so doing, the collection informs the debate on the global reform of commercial law and will be of interest also outside of academia to those involved in the reform of commercial law around the world. The volume collects papers presented at the UK Society of Legal Scholars Annual Seminar 2017"--
UNCITRAL's Role in Commercial Law Reform: History and Future Prospects / Caroline Nicholas -- The Harmonisation of Laws in the United States of America / Henry Gabriel -- Do We Need Harmonisation for Everything? : The Possibilities and Limits of Harmonising Financial Law / Souichirou Kozuka -- Behavioural Comparative Law : Its Relevance to Global Commercial Law-making / John Linarelli -- Towards a Unified Approach to Economic Assessment in International Commercial Law Reform / Jenifer Varzaly -- Cyberspace Institutions, Community and Legitimate Authority / Chris Reed -- Data-driven Mergers under EU Competition Law / Anca D Chirita -- Circular Economy, Title and Harmonisation of Commercial Law / Sean Thomas -- Service Contracts and the CISG / Ingeborg Schwenzer, Julian Ranetunge and Fernando Tafur -- The Financing of Micro-businesses in the United Kingdom : The Current Position and the Way Forward / Louise Gullifer -- Equity Crowdfunding to Facilitate Access to Finance for Small Business : The Regulatory Response and the Indirect Impact on Company Law / Teresa Rodríguez de las Heras Ballell -- Global Secured Transactions Law-making and National Law Reforms : Quo Vadis Secured Transactions Law? / N Orkun Akseli -- The Role of Innovation in Cross-Border Lending / Richard M Kohn -- Reform of Moveable Transactions Law in Scotland / Andrew Steven -- Public-Private Partnerships and Harmonisation : The Public Private Partnership Act / Richard Craven -- Regulation of Public-Private Partnership inChina : The Search for Coherence, Consistency and Certainty / Ping Wang
"The papers collected in this volume derive from a Society of Legal Scholars (SLS) seminar held at the College of St Hilde and St Bede at Durham University on 27-28 February 2017. The seminar was convened under the auspices of Durham Law School's Institute for Commercial and Corporate Law"--ECIP Introduction.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Commercial law -- International unification -- Congresses; Commercial law,Transnational commercial law; Electronic books